The Influence Of Transformational And Transactional Leadership Styles On Employee Performance Is Moderated By Psychological Capital - Alfian Ahmad Abiansyah; Ketut Sunaryanto (Publikasi Indonesia, 2023)
Employee performance can be influenced by several factors, one of which is leadership style. Leaders who have a good leadership style can improve the performance of their employees. This study aims to explore the relationship between transformational leadership style, and transactional leadership on employee performance with the moderating role of psychological capital. This research was conducted on employees who work at BPJS Ketenagakerjaan Tangerang Regency Branch, Cikupa. The research approach used in this research is quantitative research. The method used is the survey method by distributing questionnaires to all employees who work at the BPJS Ketenagakerjaan Branch of Tangerang Regency, Cikupa, totaling 50 people. The tool used in processing data in this study is using Smart-PLS version 4.0. The results of this study indicate that transformational leadership has a significant positive effect on employee performance, transactional leadership has a positive effect on employee performance, and psychological capital moderates the relationship between transformational leadership and employee performance, but in this study, it was found that psychological capital was unable to moderate the relationship between transactional leadership and employee performance